Cotton flame retardancy: state of the art and future perspectives. Issue 31 (8th April 2015) - Alongi, Jenny; Malucelli, Giulio
<x xml:space="preserve">Abstract</x> This paper reviews the most significant achievements in cotton flame retardancy merging past experience and current efforts.